1994
DOI: 10.1111/1523-1747.ep12399466
|View full text |Cite
|
Sign up to set email alerts
|

Hypomelanosis of Ito: A Description, Not a Diagnosis.

Abstract: The term hypomelanosis of Ito has been used as a diagnosis for individuals with hypopigmentation or depigmentation distributed along the lines of Blaschko. Approximately half of these patients have had neurologic, skeletal, and/or ocular abnormalities. In many, determination that the lighter areas of skin were hypopigmented rather than the darker areas hyperpigmented has been arbitrary. Evidence documenting single-gene transmission is unconvincing and recurrence risks appear to be negligible in most instances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 16 publications
0
38
0
2
Order By: Relevance
“…The skin patterns may appear as an isolated skin disorder (a pure cutaneous trait) ( pigmentary mosaicism or linear hypomelanosis [ of the Ito type ]) 24,7 or as a complex malformation syndrome in association with extracutaneous manifestations, 5,6,8 including central nervous system or musculoskeletal alterations ( hypomelanosis of Ito [HI]). 5,6,8,1116 More rarely, the eyes, heart, and genital organs can also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…The skin patterns may appear as an isolated skin disorder (a pure cutaneous trait) ( pigmentary mosaicism or linear hypomelanosis [ of the Ito type ]) 24,7 or as a complex malformation syndrome in association with extracutaneous manifestations, 5,6,8 including central nervous system or musculoskeletal alterations ( hypomelanosis of Ito [HI]). 5,6,8,1116 More rarely, the eyes, heart, and genital organs can also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Although dysfunctional pigmentation of the skin is not a common feature of ES, this association has been reported (33). Sybert (34) also found that 60 of the 115 individuals with hypomelanosis were found to have chromosomal alterations, among which mosaic trisomy 18 was the common abnormal karyotype. Collectively, these reports suggest that detection of chromosomal anomalies, including mosaicism, is warranted in patients presenting with skin depigmentation.…”
Section: Use Of Metacore For Biologic Network Analysis On a Group Of mentioning
confidence: 99%
“…A true human chimaera represents a phenotype which would potentially give a confounding result when analyzed for forensic purposes. Of the true chimaeras in the literature there are a number of possible identifying features, including ambiguous genitalia and hermaphroditism (1,23), as well as patchy skin or eye pigmentation (24). Of course this isn't necessarily the case as true chimaeras can be normal in appearance without any distinct markings to set them apart, as was shown in a case involving a maternity dispute.…”
Section: Relevance To Forensic Sciencementioning
confidence: 99%